Control of building safety through snow load monitoring - Roman Kinasz; Wiesław Bereza (Budownictwo i Architektura)
Climatic loading in the form of snow load is a significant factor for building structures. This is relevant during the design stage, the execution stage, and especially throughout the operational period. Building owners are legally required to ensure that their roofs are cleared of snow, often raising the question of whether such action is necessary in a particular situation. To address this, various devices have been developed to facilitate the systematic monitoring and measurement of snow load on roofs. These devices measure snow weight either indirectly or directly. The methods for monitoring snow weight and evaluating the effect of snow load on structural safety have been extensively discussed in the literature, considering aspects of structural integrity, operation under harsh conditions, and the economic implications of building management. In this paper, the authors propose an innovative approach to monitoring snow load using snow scales, supplemented by roof deflection measurements with tilt sensors (inclinometers). Such systems not only ensure the safety of the building and its occupants by providing reliable and verified results but also achieve this in a cost-effective manner.